Pandalungan as a Social Identity: Identity Construction, Migration, and Cultural Negotiation in Jember - Vivi Sri Rafika Umroh; Kunawi Basyir (Al-Adyan: Journal of Religious Studies, 2026)
This article examines the construction of Pandalungan cultural identity in Jember as a product of interaction, acculturation, and cultural negotiation between the Madurese and Javanese communities. Employing a qualitative approach with an acculturative anthropological perspective, the study explores how migration, social interaction, social construction, cultural acculturation, and identity negotiation have shaped the formation of Pandalungan identity. Data were collected through in-depth interviews with cultural figures, historians, and community leaders representing the Pandalungan community in Jember, complemented by a review of relevant literature. The analysis draws upon Peter L. Berger's theory of social construction, the cultural acculturation models of the Melting Pot and Salad Bowl, and Homi K. Bhabha's concept of cultural hybridity. The findings reveal that the social construction of Pandalungan culture has evolved through Berger's three dialectical processes-externalization, objectification, and internalization-resulting in a hybrid culture with distinctive characteristics reflected in language, social traditions, religious rituals, social structures, and shared values. Furthermore, the official declaration of Jember as the "City of Pandalungan" in 2016 reinforced the social and cultural legitimacy of this identity within the local community. The study concludes that Pandalungan culture is not merely the outcome of cultural acculturation but represents a dynamic, negotiated, and evolving cultural identity that continues to adapt to social transformation and modernization within contemporary society. Artikel ini bertujuan untuk mengkaji konstruksi identitas budaya Pandalungan di Jember sebagai hasil interaksi, akulturasi, dan negosiasi budaya antara masyarakat Madura dan Jawa. Penelitian kualitatif yang menggunakan pendekatan antropologis akulturatif ini menjelaskan bagaimana proses migrasi, interaksi dan konstruksi sosial, akulturasi budaya serta negosiasi identitas berlangsung antara masyarakat Madura dan Jawa. Penelitian ini menggunakan metode kualitatif dengan pendekatan antropologis dan fokus pada kajian akulturasi budaya. Data diperoleh melalui wawancara mendalam dengan tokoh budaya, sejarawan, dan tokoh masyarakat Pandalungan di Jember, serta didukung oleh studi literatur yang relevan. Analisis penelitian menggunakan teori konstruksi sosial Peter L. Berger, teori akulturasi budaya Melting Pot dan Salad Bowl, serta konsep hibriditas Homi K. Bhabha. Hasil penelitian menunjukkan bahwa konstruksi sosial budaya yang terjadi antar masyarakat migran berlangsung melalui tiga tahap dialektika yaitu eksternalisasi, objektivasi dan internalisasi yang mampu menciptakan budaya hybrid dengan karakteristik dan khas dalam aspek bahasa, tradisi sosial, ritual keagamaan, struktur dan nilai sosial. Selain itu, deklarasi Jember sebagai "Kota Pandalungan" pada tahun 2016 semakin memperkuat legitimasi sosial dan kultural identitas tersebut dalam masyarakat. Dengan demikian budaya Pandalungan bukan hanya sekadar hasil akulturasi budaya semata, tetapi juga sebuah identitas budaya yang bersifat dinamis, negosiatif, dan mampu berkembang mengikuti perubahan sosial masyarakat serta modernisasi di era kontemporer dalam ruang sosial masyarakat.